A methodology for the pre-clinical evaluation of patellar implants. (11th November 2009) - Kersh, Mariana E.; Ploeg, Heidi-Lynn
A methodology for the alignment of patellar and femoral components in pre-clinical test of patellar components used in total knee arthroplasty is presented. The component alignment was based on kinematic degrees of freedom that should be considered to recreate clinically relevant patello-femoral contact patterns. A literature review of patellar kinematics revealed that patellar motion occurs in all six degrees of freedom. Retrieval studies reported that deformation was most prominent on the lateral aspect of the patellar component and in contact regions that occur at higher degrees of knee flexion. Based on this review, it was hypothesised that alignment of the patellar and femoral components should incorporate patellar flexion, proximal-distal translation, anterior-posterior translation and medial-lateral translation. The efficacy of the model was tested by evaluating its ability to create physiological contact patterns in patellar components used in total knee arthroplasty. Two types of components were tested: metal-backed dome and all-polyethylene sombrero-shaped of which the dome-shaped components have a higher reported incidence of failure. The component alignment method resulted in higher contact areas in the sombrero-shaped components than the dome-shaped. Contact patterns of both components were compared to contact patterns reported in the literature for natural and implanted patellae and compared favourably.